Temporal trend analysis of hospitalizations and in-hospital deaths due to female breast cancer in the state of Alagoas from 2009 to 2019: a cross-sectional study - Leão, Myra Jurema da Rocha; Cardoso, Vitória Ingryd dos Santos; Lima, Ayara Jhulia Palmeira Dantas; Santos, Samilla Cristinny; Araújo, Emmylly Maria Correia Ferro de; Paixão, Karen da Costa; Santos, Lucas Gomes; Fraga, Carlos Alberto de Carvalho; Souza, Carlos Dornels Freire de; Marques, Carolinne de Sales (São Paulo Medical Journal, 2022)
BACKGROUND: Breast cancer is a common neoplasm in women worldwide. Its varying patterns of incidence and clinical prognosis in Brazil make it an important and complex public health problem that needs to be solved. OBJECTIVES: To analyze the temporal dynamics of hospital admissions and deaths due to female breast cancer in the state of Alagoas, Brazil, from 2009 to 2019. DESIGN AND SETTING: Cross-sectional study including secondary data from hospital admissions and deaths due to female breast cancer in Alagoas. METHODS: A joinpoint regression model was constructed for temporal analysis of hospital admissions and deaths due to female breast cancer in Alagoas, over this period. The hospital information system of the Department of Informatics of the National Health System was used. RESULTS: There were 5,801 hospitalizations and 633 hospital deaths due to neoplasm in Alagoas over the period. The age group from 50 to 59 years old stood out, corresponding to 28.1% of hospitalizations and 31.1% of registered deaths. An increasing trend in the rate of hospital admissions was observed (average annual percentage change, AAPC = 14.0; P-value < 0.001), from 14.9/100,000 inhabitants in 2009 to 53.6 in 2019. There was a growth trend in the in-hospital mortality rate (AAPC = 19.8; P-value < 0.001), from 6.3% in 2009 to 11.0% in 2019. CONCLUSION: The results indicated an increasing trend of hospital admissions and mortality rates in the state of Alagoas, with a higher percentage of hospitalizations and deaths in the 50-59 age group.